2020
DOI: 10.1186/s12887-020-02284-6
|View full text |Cite
|
Sign up to set email alerts
|

Careful conversations: an educational video to support parents in communicating about weight with their children

Abstract: Background Parents may struggle to initiate healthy weight-related conversations with their children. Educational videos may be an effective tool for improving parents’ knowledge and self-efficacy on this topic. The aim of this pilot study was to develop an educational video to assist parents in weight-related conversations with their child, and to assess changes in parents’ self-efficacy on this topic. Methods Video development was based on a scoping review and semi-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“… 31 Whiteboard-style videos, including visual depiction of the intervention, might also be useful; such videos have shown promise in increasing parents' and HCPs' self-efficacy in communicating about weight and weight management. 36 , 37 We hypothesize that adequate parental understanding of the intervention would facilitate STOMP-EY implementation by increasing engagement and decreasing attrition.…”
Section: Discussionmentioning
confidence: 99%
“… 31 Whiteboard-style videos, including visual depiction of the intervention, might also be useful; such videos have shown promise in increasing parents' and HCPs' self-efficacy in communicating about weight and weight management. 36 , 37 We hypothesize that adequate parental understanding of the intervention would facilitate STOMP-EY implementation by increasing engagement and decreasing attrition.…”
Section: Discussionmentioning
confidence: 99%
“…Robinson et al (2017) found that parents' perception of their children as overweight increases the likelihood that children will negatively view and recognize their body size. Additionally, compared with parents without concern for their children's weight, parents who had concerns were identified with significantly lower perceived self-efficacy (Klupt et al, 2020), which may unavoidably influence the children's own weight-related perceptions. Therefore, it is essential to understand the parent's influence on profound perceptions when considering why the perceived stigma is positively correlated with parent-rated weight-related QoL.…”
Section: Perceived Weight Stigma and Quality Of Lifementioning
confidence: 99%
“…Parents may view YouTube as having advantages for accessing educational content, as YouTube is free, accessible (Azer et al, 2018) and may be used as a tool to easily disseminate knowledge (Campbell‐Yeo et al, 2017). In studies of health education, educational videos have been shown to not only enhance parents' understanding of a topic (eg, Azer et al, 2018; Spoyalo et al, 2021) but also their self‐efficacy (Klupt et al, 2020). For example, Spoyalo et al (2021) found that parents seeking medical knowledge desired educational videos that were accessible (ie, easy to find), come from a trusted source, are positive, and relevant.…”
Section: Addressing Parents' Misconceptions With An Educational Videomentioning
confidence: 99%